The Effect of Ginseng Extract Supplementation on Procalcitonin Level, Neutrophil, and Length of Stay In Patients With Community Acquired Pneumonia - Anita Ramlie; Reviono Reviono; Jatu Aphridasari (Respiratory Science, 2022)
Background: Pneumonia is an acute inflammation of the lung parenchyma caused by microorganisms (bacteria, viruses, fungi, parasites) and causes of high morbidity and mortality. Ginsenoside in ginseng have anti-inflammatory effects, potentially as adjunctive therapy in community-acquired pneumonia (CAP) patients. As much as 43% of patients at dr. Moewardi Hospital in 2016 were hospitalized have passed away. The aim of this study was to determine the effect of ginseng extract on levels of procalcitonin, neutrophils, and length of stay of community-acquired pneumonia patients. Method: The quasi-experimental clinical trial with the pretest posttest design approach was conducted on 26 community acquired pneumonia patients who were hospitalized in Dr. Moewardi Hospital Surakarta from October until November 2019 using consecutive sampling. The control group (n=13) received standard antibiotics while the treatment group (n=13) received additional ginseng extract 2x100 mg/day for 14 days. Procalcitonin was measured at admission, third and fourteenth day; neutrophils are measured at admission and third day; length of stay is based on the number of days of treatment in hospital. Results: There was a significant difference (P=0.001) towards decreased of serum procalcitonin levels between treatment group    (-0.63±0.06) compared to control group (-0.38±0.07). There was a significant difference (P<0.001) towards decreased of neutrophil levels between treatment group (-6.68±1.34) compared to control group (-3.51±0.88). There was a significant difference (P=0.001) towards decreased of length of stay between treatment group (5.69±0.95) compared to control group (7.15±0.99). Conclusion: Ginseng extract containing ginsenoside as its main ingredient, can act as an anti-inflammatory which can be used as adjunctive therapy in community-acquired pneumonia patients who are hospitalized to accelerate clinical improvement and shorten the length of stay.